ANALISIS PEMASARAN KOPRA DI DESA LEMBAH MUKTI KECAMATAN DAMPELAS KABUPATEN DONGGALA - Devi Eka Handayani; Christoporus Christoporus; Hardianti Sultan (Universitas Tadulako, 2022)
This study aims to determine the form of marketing channels, marketing margins, the share of prices received by farmers and the efficiency of copra marketing in Lembah Mukti Village, Dampelas District, Donggala Regency. This research was conducted from October to December 2019 in Lembah Mukti Village, Dampelas District, Donggala Regency. Respondents who were sampled consisted of copra producers, traders and wholesalers collectors. A sampling of copra producers was carried out using the simple random sampling method as many as 33 producers (farmers) from a total population of 130 respondents who worked on copra, then sampling traders were carried out using the tracing sampling method so that 2 people were obtained. Are 2 trader, 1 wholesaler. The data used are primary data and secondary data. The analysis used in this research is marketing analysis which contined marketing channels, marketing margins, the share of prices received by farmers and marketing efficiency. The results of the marketing analysis showed that the copra marketing channels in Lembah Mukti Village were through two marketing channels, the channels of the first one are Farmer-trader-wholesaler in the channels of the second one are Farmer-Big Trader. The result of the first channel copra marketing margin analysis is MT = Rp. 1,200 / Kg while the second channel is MT = Rp. 500 / Kg. The share of prices received by copra farmers is on the first channel which are 76.00%, meanwhile on the second channel that is, 90.00%. Marketing Efficiency on the first channel was 27.8%, while the efficiency value the second channel was 21.4%, so between that two channels, the most efficient channel are the second one with the value of efficiency is 21.4%.